La forteresse de Sadr, une lecture géo-historique au temps des croisés - Corinne Feïss-Jehel; Jean-Michel Mouton; Claudine Piaton; Pierre-Jérôme Jehel; Jeannine Le Rhun (EchoGéo)
At the heart of the Sinai desert lies the Sadr fortress, today called Qal-at al-Gindi, is the most authentic archeological legacy left in the Middle East by the famous Kurdish sovereign Saladin (1174-1193). This military edifice was built in the context of the crusades. The organization of the east-west crossings of the Sinai was in fact going through a major change in the twelfth century.The low coastal route along the Mediterranean provided a quick and easy way for Muslim caravans traveling between Egypt and Syria. The littoral plain of Gifar offered a dune belt that was relatively flat compared to the mountains of central Sinai. This road, a main route for centuries, came under partial control of the Frankish states in 1099 with the creation of the Latin Kingdom of Jerusalem. The Latin hold became a more impassible obstacle than the physical barriers of the Sinai. Saladin therefore set up an inner route that made the journey between Africa and Muslim Asia slower and harder but safer. Little by little, control over physical constraints began to work against the crusaders. The location of the Sadr fortress appears to have met two major geographic criteria. Firstly, construction on a high butte gave the fortress a strong defensive position with a commanding view of the lower areas, which were the only way an army could approach. Secondly, the fortress's location provided exceptional access to fresh water. The Sadr fortress in central Sinai, in the Wâdi-al-Sudr valley eighty kilometers from the Gulf of Suez, was built on and for the central Sinai route. Midway between Cairo and the Ayla fortress, it constituted a vital stopover for Saladin in an extremely harsh and arid region.